Pengaruh Konsentrasi Ekstrak Biji Kakao Terhadap Diameter Zona Bening Pada Bakteri Streptococcus Mutans - Iza Alfi Rohmatin; Suparno Suparno (Jurnal Penelitian Pendidikan IPA, 2023)
Cocoa beans can inhibit the growth of pathogenic bacteria such as Streptococcus Mutans. Utilization of cocoa bean extract as an anti-bacterial inhibitor containing chemical compounds extracted in simplicia aims to increase the content in the form of alkaloids, flavonoids, tannins, saponins and polyphenols. Streptococcus Mutans is a gram-positive facultative anaerobic coccus that is usually found in the human oral cavity and one of the causes of tooth decay or cariogenic bacteria capable of creating an acidic atmosphere in the mouth and can metabolize carbohydrates. This paper describes the effect of the concentration of cocoa bean extract on the diameter of the clear zone of Streptococcus Mutans bacteria. The antibacterial test was carried out using the Mueller Hinton Agar (MHA) method, samples of cocoa bean extraction were prepared by maceration method with varying concentrations of 2.5% to 12.5% ​​at 2.5% intervals. With an interval of three hours, measurements were carried out for 48 hours of observation. The results showed that the greater the concentration of cocoa bean extract, the larger the diameter of the clear zone, with the smallest diameter (8.44 ± 1.61) mm (for a concentration of 2.5%) and the largest diameter (9.70 ± 1.66) mm (for a concentration of 12.5%).